Self-Concept and Stigma in Narcotics Addicts in Clinics Pratama Narcotics Rehabilitation LRPPN BI Medan - Maria Fransiska Octaviani Silaen; Jenny Marlindawani Purba (Health and Technology Journal (HTechJ), 2023)
Drug addicts during their rehabilitation encounter problems regarding how people label them which is called “stigma” which can affect the drug addicts’ self-concept. The research aims to find out the self-concept and stigma of Drug Addicts in Pratama Drug Rehabilitation Clinic of LRPPN BI Medan. This descriptive quantitative research is conducted in Pratama Drug Rehabilitation Clinic of LRPPN BI Medan using a total sampling technique. The research questionnaires consist of demographic questionnaires, self-concept questionnaires, and internalized stigma questionnaires. The result indicates that the self-concept of 58 respondents (93,5%) falls in a positive category and 4 respondents (6,5%) fall in a negative category. Meanwhile, 34 respondents (54,4%) feel a negative stigma from the society. It is recommended that society not label or give a negative stigma on drug addicts but motivate them to have self-confidence and motivate them to recover from addiction.